KONSUMERISME DALAM PERSPEKTIF HUMAN DEVELOPMENT - Rannie Rachaju (Dialektika, 2017)
Information has become an ever-increasing needs. The public consumes information every day, from anywhere and in any way. The need for this communication is increasingly facilitated by the development of communications technology. Encouraged the community to have the communication tools that its content and not yet fully understand the functions and benefits or (regrettably) only inedible prod trendsetters and are tempted to follow the pattern of urban lifestyle. Lower class people who want to follow the lifestyle of leisure group class then becomes 'victim'. They became consumptive and hunting for items they do not really understand fully. They became consumptive and trying to follow the class leisure lifestyle they do not really understand fully.